2017
DOI: 10.1038/s41598-017-08572-z
|View full text |Cite
|
Sign up to set email alerts
|

Mussel Inspired Polynorepinephrine Functionalized Electrospun Polycaprolactone Microfibers for Muscle Regeneration

Abstract: Electrospun scaffolds with excellent mechanical properties, high specific surface area and a commendable porous network are widely used in tissue engineering. Improving the hydrophilicity and cell adhesion of hydrophobic substrates is the key point to enhance the effectiveness of electrospun scaffolds. In this study, polycaprolactone (PCL) fibrous membranes with appropriate diameter were selected and coated by mussel-inspired poly norepinephrine (pNE). And norepinephrine is a catecholamine functioning as a hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…The significance of polydopamine was quickly realized resting on its capability to adapt to various surface functions. This behavior was also observed for other catecholamines, such as l ‐3,4‐dihydroxyphenylalanine ( l ‐DOPA) and norepinephrine . Chemically, polycatecholamine films possess important functional groups including amines, alcohols, and conjugated Michael acceptors leading to a massive variety of post‐functionalized surfaces .…”
Section: Introductionmentioning
confidence: 74%
“…The significance of polydopamine was quickly realized resting on its capability to adapt to various surface functions. This behavior was also observed for other catecholamines, such as l ‐3,4‐dihydroxyphenylalanine ( l ‐DOPA) and norepinephrine . Chemically, polycatecholamine films possess important functional groups including amines, alcohols, and conjugated Michael acceptors leading to a massive variety of post‐functionalized surfaces .…”
Section: Introductionmentioning
confidence: 74%
“…Incorporation of small molecules or single growth factor is one of the simplest way to load therapeutics into scaffolds for better performances. For better skeletal muscle regeneration, Liu et al coated PCL fibers with mussel‐inspired poly‐norepinephrine (pNE), a catecholamine functioning as a hormone and neurotransmitter in the human brain, to obtain fiber surfaces enriched with catechol groups that attract primary amine or thiol‐based biomolecules. Their study revealed that fiber meshes with thinner fiber diameter could be more effectively functionalized by pNE, and thus had higher muscle cell proliferation and adhesion and treatment efficacy for repairing impaired musculus rectus abdominis in a rat muscle injury model.…”
Section: Applications In Biomedical Fieldsmentioning
confidence: 99%
“…Both porous network and high surface-to-volume ratio are in favour of cellular attachment, migration and proliferation. In addition, good permeability of oxygen, carbon dioxide and water, outputting of metabolic waste and effective inhibiting pathogen invasion are the additional advantages of the fibrous membrane matrix [7,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%